Corporate social responsibility (CSR) practices in large manufacturing firms: a qualitative multi-case study from Ethiopia - Habtie Alemnew Belay; Fentaye Kassa Hailu; Gedif Tessema Sinshaw (Cogent Business & Management, 2024)
Assessment of actual practices and initiatives would potentially enhance the implementation of corporate social responsibility. For the same purpose, this work aimed at enumerating specific CSR activities being pursued by large manufacturing businesses and detecting whether there have been observed developmental changes in CSR practices in the industry. To this end, we have devised a multi-case study research design. Because they needed attention of inquiry, large manufacturing firms in the Amhara region of Ethiopia constituted the target units. The recent corporate social responsibility practices of four purposefully selected firms have been judged by functional managers and report analysis. The hybrid of deductive—theory-driven data collection and data analysis—and inductive approaches governed the inquiry. We utilized a stakeholder-based Corporate Social Responsibility (CSR) conceptual framework from the existing literature. The results of a stakeholder-based analysis of CSR practices show that: (1) the industry has implemented numerous CSR initiatives and activities for each of the stakeholder groups; (2) developmental changes in CSR performance are observed; and (3) healthy (responsible) business behavior has generally been evident. Notwithstanding its limitations, the study has provided useful insights into both practice and policymaking. Similar studies with tailored designs are encouraged for future research.There exists a clear link between businesses as institutions and society. The effect is bilateral: businesses affect the state of a society, and the society can grant or lift up legitimacy for businesses. Thus, the extent to which either of the parties are discharging the responsibilities for the other party need to be examined. This particular study has found itself in the first line of inquiry: examining the extent to which selected businesses in the country of Ethiopia, particularly in the Amhara region of the country, have been responsible to society (which has been expressed in terms of stakeholders), and enumerating the numerous initiatives these companies have been pursuing for the same group of stakeholders (operationalization of society). This piece of knowledge would be useful for both the businesses to see their track and to the society to lift up, or otherwise, its legitimacy. Apart from practical contribution, the study would contribute to the theory of business and society in its insight into the integration of stakeholder and CSR theories, yielding a multi-stakeholder approach to CSR inquiry.
Keywords: 650; Stakeholder theory; social responsibility; business ethics; corporate citizenship; business and society; business in society